2007
DOI: 10.1159/000112541
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression in Response to Bacterial Antigens in Preterm and Term Infant Cord Blood Monocytes

Abstract: Background: Neonatal susceptibility to bacterial infection is associated with an immature immune system, but the role of different bacterial antigens in specific responses is largely unknown. Objective: To evaluate differences in intracellular cytokine response to physiologically relevant bacterial antigens in term and preterm infants as compared with adults. Methods: Cord blood samples from preterm and term neonates and adult peripheral blood samples were cultured ex vivo with and without whole heat-killed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
1
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 85 publications
6
31
1
1
Order By: Relevance
“…This suggests that the blood monocyte compartment of healthy, term infants is functionally competent in recognizing and responding to GBS. Several studies have demonstrated equivalent or greater inflammatory production by term MNC (in CBMC or whole blood) after GBS stimulation (27,47), with cytokine production predominantly monocyte derived (35,40,44). Our data, derived using live bacteria over a range of inocula, are therefore consistent with GBS exposure resulting in an overt inflammatory response in the newborn (16).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This suggests that the blood monocyte compartment of healthy, term infants is functionally competent in recognizing and responding to GBS. Several studies have demonstrated equivalent or greater inflammatory production by term MNC (in CBMC or whole blood) after GBS stimulation (27,47), with cytokine production predominantly monocyte derived (35,40,44). Our data, derived using live bacteria over a range of inocula, are therefore consistent with GBS exposure resulting in an overt inflammatory response in the newborn (16).…”
Section: Discussionsupporting
confidence: 83%
“…Similar GA-dependent responses are reported following LPS stimulation (6), with infants with a GA of Ͻ32 weeks having a lower proportion of IL-6-producing monocytes (35). A recent study examining intracellular cytokine responses to GBS and other bacterial stimuli in preterm infants did not find a significant impairment in IL-6, -8, -10, and -12 production in comparison to that of term infants or adults, although responses were monocyte driven (40). However, the levels of secreted cytokines produced by each group were not measured, and the study did not distinguish between extreme and moderate preterm infants.…”
Section: Discussionsupporting
confidence: 60%
“…However, differences in the study design regarding incubation times and their use of planktonic SE instead of the biofilm used in our study may explain these differences. Tatad et al showed that after stimulating monocytes for 18 h with SE, there was a significantly higher secretion of IL-6, IL-8, and IL-12 in adult blood as compared with blood from term neonates (35). It is possible that the adult cytokine secretion would reach the same level as that of neonates if longer incubation times had been used in our …”
Section: Discussionmentioning
confidence: 77%
“…During neonatal infections, an exacerbated inflammatory response often occurs inducing the enhanced release of proinflammatory cytokines and chemokines, which may lead to septic shock and death (12,13). In fact, expression levels of TLR4 control the magnitude of the response to LPS.…”
mentioning
confidence: 99%